2016
DOI: 10.1111/aos.13033
|View full text |Cite
|
Sign up to set email alerts
|

Serum anti‐endothelial cell antibodies in patients with age‐related macular degeneration treated with intravitreal bevacizumab

Abstract: There is growing evidence that AMD is an immune-mediated disease, and thus it cannot be excluded that AECA may be involved in its pathogenesis and progression. We also speculate that AECA develop in response to retinal damage and anti-VEGF therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
(31 reference statements)
2
7
0
Order By: Relevance
“…(Kubicka‐Trzaska et al. ) Also, a variant of the complement factor H (CFH) gene, which causes uncontrolled complement activation, has been linked to AMD. (Nussenblatt et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Kubicka‐Trzaska et al. ) Also, a variant of the complement factor H (CFH) gene, which causes uncontrolled complement activation, has been linked to AMD. (Nussenblatt et al.…”
Section: Introductionmentioning
confidence: 99%
“…(Heckenlively et al 1999) Decrease in serum ARA levels was reported after intravitreal antivascular endothelial growth factor (VEGF) therapy in AMD. (Kubicka-Trzaska et al 2016) Also, a variant of the complement factor H (CFH) gene, which causes uncontrolled complement activation, has been linked to AMD. (Nussenblatt et al 2013) The presence of ARAs in aqueous humour and serum has been observed in patients with glaucoma and in neurodegenerative damage of the optic nerve.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Recent investigations have demonstrated that the concentration of AECA decreases in patients receiving bevacizumab. [14] Moreover, high expression of VEGF was reported in patients with vasculitis and in children with acute-phase IgAV. [15,16] Some reports suggest that bevacizumab administration is unlikely to lead to the development of IgAVN.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, organ-specific autoreactivity (ARA) appears to be suppressed in both active and latent TB; however, the local production of ARA in ocular fluid samples was not investigated in this series. The presence of serum autoantibodies, directed against endothelial cells, and their decrease following treatment were reported in age-related macular degeneration (Kubicka-Trzaska et al 2016). Unfortunately, we have no samples of our patients after they completed the treatment.…”
Section: Referencesmentioning
confidence: 91%